Experimental Analysis of Green Paver Block using Waste Material - Divyarth Manas, Himanshu Agrawal, Krishna Deep, Vidhi Sharma, Barkha Soni, Anant Kumar (Mathematical Statistician and Engineering Applications, 2022)
the concrete industry in India is expanding to meet the demand for systematic and cost-effective construction materials as a result of increased industrialization and urbanization processes. In this research work, we tried to find the replacement of cement and fine aggregate used in conventional concrete paver block, by industrial wastes like fly ash and wood powder, as a huge amount of construction work has been led to the shortage of natural aggregates and also, we all are aware of the harmful carbon emission due to cement construction. Cement was partially mixed with fly ash and sand (specifically the organic content) was replaced with wood powder. The materials were replaced in the proportion of 5%, 8% and 10%. This concrete paver block was made up of M-25 grade and the mix ratio of 1: 1.74: 2.11 was calculated. Three cubes for each percent replacement were prepared, placed in curing for 7, 14, and 28 days, and then different tests like compressive strength tests, slump cone test, etc. were performed. The water-cement ratios required for 5%, 8% and 10% were 0.48, 0.55 and 0.58. The strength found out by testing was found to be sufficient and was similar to the nominal strength of concrete paver block of similar ratio, and hence it is convenient to use. This will solve the problem of shortage of natural aggregates as well as the waste management.